Polish adaptation of the questionnaire for measuring character strengths International Personality Item Pool – Values in Action (IPIP-VIA). Preliminary results. - Najderska, Małgorzata; Cieciuch, Jan (Studia Psychologica: Theoria et praxis, 2013)
In 2004 Peterson and Seligman presented their concept of virtues and 24 character strengths which are widely-valued positive characteristics considered to be important for achieving a good, happy life (Peterson, Seligman, 2004). For their measurement Peterson and Seligman (2004) developed Values in Action – Inventory of Strengths (VIA-IS). As a part of his International Personality Item Pool project (ipip.ori.org), Goldberg developed his own measurement of Peterson and Seligman’s character strengths, which differs from VIA-IS for example in its open access form. Research on Polish version of the International Personality Item Pool – Values in Action questionnaire (IPIP-VIA) was conducted on a sample of N = 908 adults. It proved satisfactory psychometric properties of the tool. High or satisfactory reliability for all the scales measuring character strengths was achieved. Validity of the tool was tested by comparing sex differences obtained in research with a Polish version of the IPIP-VIA and the results of studies conducted in the UK with the VIA-IS questionnaire.